Cathepsin B as a potential cystatin M/E target in the mouse hair follicle. Issue 10 (19th September 2017) - Oortveld, Merel A. W.; van Vlijmen‐Willems, Ivonne M. J. J.; Kersten, Ferry F. J.; Cheng, Tsing; Verdoes, Martijn; van Erp, Piet E. J.; Verbeek, Sjef; Reinheckel, Thomas; Hendriks, Wiljan J. A. J.; Schalkwijk, Joost; Zeeuwen, Patrick L. J. M.
ABSTRACT: Deficiency of the cysteine protease inhibitor cystatin M/E (Cst6) in mice leads to disturbed epidermal cornification, impaired barrier function, and neonatal lethality. We report the rescue of the lethal skin phenotype of ichq (Cst6‐deficient; Cst6 −/− ) mice by transgenic, epidermis‐specific, reexpression of Cst6 under control of the human involucrin (INV) promoter. Rescued Tg(INV‐ Cst6 ) Cst6 ichq/ichq mice survive the neonatal phase, but display severe eye pathology and alopecia after 4 mo. We observed keratitis and squamous metaplasia of the corneal epithelium, comparable to Cst6 −/− Ctsl +/− mice, as we have reported in other studies. We found the INV promoter to be active in the hair follicle infundibulum; however, we did not observe Cst6 protein expression in the lower regions of the hair follicle in Tg(INV‐ Cst6 ) Cst6 ichq/ichq mice. This result suggests that unrestricted activity of proteases is involved in disturbance of hair follicle biology, eventually leading to baldness. Using quenched activity‐based probes, we identified mouse cathepsin B (CtsB), which is expressed in the lower regions of the hair follicle, as an additional target of mouse Cst6. These data suggest that Cst6 is necessary to control CtsB activity in hair follicle morphogenesis and highlight Cst6‐controlled proteolytic pathways as targets for preventing hair loss.—Oortveld, M. A. W., van Vlijmen‐Willems, I. M. J. J., Kersten, F. F. J., Cheng, T., Verdoes, M., van Erp, P. E. J., Verbeek, S., Reinheckel, T., Hendriks, W. J. A. J., Schalkwijk, J., Zeeuwen, P. L. J. M. Cathepsin B as a potential cystatin M/E target in the mouse hair follicle. FASEB J. 31, 4286–4294 (2017). www.fasebj.org